2009
DOI: 10.1590/s0104-42302009000600019
|View full text |Cite
|
Sign up to set email alerts
|

Efetividade da metilprednisolona na fase aguda do trauma raquimedular: revisão sistemática dos ensaios clínicos randomizados

Abstract: Steroid therapy has been tested as a neuronal protector in spinal cord injury. Multicenter studies evaluating the efficacy of methylprednisolone (MP) in posttraumatic neurological recovery have shown promising results (NASCIS). However, several critical studies related to NASCIS results have been published. Objective. To review the literature concerning the use of methylprednisolone compared with placebo. MethOds. This analysis added the mean improvement obtained by groups of patients using MP and placebo (PL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Bracken and Botelho and colleagues have each reported on meta-analyses that evaluate the effect of methylprednisolone against placebo in patients with TSCIs, but the conclusions from these studies are conflicting and each is limited by poor methodological credibility. 15 , 59 Neither ensured that the selection of studies was reproducible, neither explored possible explanations for between-studies differences in results, and neither study addressed the overall quality of the evidence or confidence in the pooled estimates. 58 According to the Grades of Recommendation, Assessment, Development and Evaluation (GRADE) approach, confidence in pooled effect estimates depends on study design, risk of bias, imprecision, inconsistency, indirectness, publication bias, and other factors.…”
Section: Discussionmentioning
confidence: 99%
“…Bracken and Botelho and colleagues have each reported on meta-analyses that evaluate the effect of methylprednisolone against placebo in patients with TSCIs, but the conclusions from these studies are conflicting and each is limited by poor methodological credibility. 15 , 59 Neither ensured that the selection of studies was reproducible, neither explored possible explanations for between-studies differences in results, and neither study addressed the overall quality of the evidence or confidence in the pooled estimates. 58 According to the Grades of Recommendation, Assessment, Development and Evaluation (GRADE) approach, confidence in pooled effect estimates depends on study design, risk of bias, imprecision, inconsistency, indirectness, publication bias, and other factors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies reviewing the methodologies used in NASCIS and other research projects reported the deleterious side effects of massive doses of corticosteroids. These side effects have led many centers to avoid routinely using corticoids, particularly methylprednisolone (53), for SCI lesions (52). …”
Section: Therapeutic Possibilitiesmentioning
confidence: 99%
“…[25] However, many methodological biases were pointed later by other authors, suggesting that the benefits of corticosteroids were minimal when compared to the potential catastrophic complications. [262728] Furthermore, the studies included both cervical and thoracolumbar spinal cord injuries without independent data reporting. In this context, the use of methylprednisolone is not accepted as a standard therapy in many centers.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%